O reflexo da gestão de riscos na governança: um estudo sobre as compras da Unila - Sturmer, Robinson Alexander (2022)
The traditional view of the Public Administration on the role of risk management, especially when it comes to procurement - focuses on the actors in the bidding process, as Brazilian legislation has as its primary concern the fight against corruption. It happens that it is not restricted to this role only, since political, operational, environmental, financial and other factors place purchases as one of the most vulnerable governmental activities to risks. Governance of this process is necessary, and risk management has the ability to promote this improvement, as it supports management decisions, increases efficiency in the use of resources and institutional performance, among others. Considering this view, it becomes relevant to discuss risk management at an operational level in the purchases of a Federal University, since this environment consumes a significant portion of the institution's financial and human resources. In this way, the general objective of this research is to discuss the management of risks in purchases and its reflexes in relation to the governance of the process and the specific objectives seek to identify the main actors through the mapping of the process; understand, based on ISO 31000, how risks are identified and managed in the purchasing process; and, investigate which governance mechanisms are present in the process. The research methodology has an applied, descriptive nature and was implemented by a case study with a qualitative approach. As for the results, it was possible to observe that there is a formalized risk management structure focused on the integrity of the process, but considering exclusively the purchasing activity, the data indicate that the risk management culture is present and active in the institution, since the actors instruct the purchase with the help of checklists and exchange experiences with the others involved. Another relevant aspect observed is the lines of defense, which in addition to managing risks, contribute to governance, as the way the process flows promotes a reasonable guarantee of success in acquisitions and has the potential to reduce situations that affect the outcome of the intended acquisition. Finally, and considering that risk management is a fundamental part of controls and one of the pillars of governance, it can bex concluded that in the observed environment it is largely responsible for consolidating the institution's planning, therefore, strategic to achieve the desired objectives. This is where risk management reflects on governance, especially in terms of controls, as in Unila's case they are incorporated into the process, in an agile and collaborative way that mitigates risks and aims to preserve integrity, legality, economy and efficiency. of the purchase, contributing positively to the achievement of the objectives. In terms of expectations regarding the results of this study, it is expected that they can serve as a stimulus for the activity of risk management in other Brazilian Universitie s, strengthening institutions in the face of typical adversities of the public sector.